CITRA KOSMETIK DALAM IKLAN SHISEIDO "THE SECRET OF HIGH SCHOOL GIRLS” - Dita Ristanti (Japanology: The Journal of Japanese Studies, 2019)
Image is an ideal picture of something. In commercial there are several types of images that are often displayed, including women's image, masculine image, luxury and exclusive image, social class image, pleasure image, benefit image, friendship image, and sexuality image. One example of a commercial that displays an image is a cosmetic commercial. The image displayed in general cosmetic commercial is the image of beauty through certain beauty criteria or standards. The image of beauty itself is classified as a form of women's image which illustrates that every woman always wants to look beautiful. In Japanese cosmetics commercial Shiseido "The Secret of High School Girls", to promote Shiseido women's beauty products using men as a model. The presence of female cosmetic commercial featuring men as a model made the writer interested in seeing how the image of cosmetics produced through the use of the male model. This study aims to analyze the image of cosmetics that appeared in Shiseido's cosmetic commercial "The Secret of High School Girls". This study uses qualitative research methods as a research method, and uses the method of documentation and literature in data collection. Documents in the form of pieces of scenes or scenes from Shiseido's commercial video "The Secret of High School Girls" were then analyzed using concepts such as the concept of advertising images and the concept of beauty of joshi kousei. The results of this study are 1) the image of Japanese beauty that is used as a standard of beauty by Shiseido is the beauty of joshi kousei who is portrayed as a young, fresh, and beautiful figure with maximum makeup; 2) the image of Shiseido's cosmetic benefits shown by the greatness of Shiseido's cosmetic products through the transformation process of turning men into joshi kousei.